Topical Use of Tranexamic Acid in Cardiac Surgery: A Meta-Analysis - Habbab, Louay M.; Semelhago, Lloyd; Lamy, André (The Thoracic and Cardiovascular Surgeon, 2020)
Background This meta-analysis was conducted to investigate the evidence for the efficacy and safety of intrapericardial tranexamic acid (TXA) in cardiac surgery.Methods We searched MEDLINE from 2000 to 2017 for randomized controlled trials that compared intrapericardial TXA to placebo. We performed a meta-analysis for the eligible trials that focused on chest tube drainage measured during the first 24 hours after surgery as a primary outcome. We also examined the secondary outcome measures of these trials such as the incidence of transfusion requirements following surgery and the evidence for any increase in complication rates.Results A total of seven randomized controlled trials (six on-pump and one off-pump) comparing topical application of TXA to placebo in 692 patients were eligible for the blood loss outcome data. These trials randomized 372 patients to receive TXA and 320 patients as controls. The use of intrapericardial TXA was associated with a considerable reduction in 24-hour blood loss in all seven studies and a weighted mean difference of −343.56 mL (95% confidence interval: −316.41, −370.72) significantly differed from zero (p = 0.005) with a heterogeneity of I2 = 0%. The incidence of packed RBC transfusion in TXA patients was significantly lower in one study and was not significant but with trend in favor of TXA in five out of the six studies in which it was reported. In one trial, TXA was not detected in any patient and in another the studied groups were similar in postoperative complications, such as graft patency, myocardial infarction, cerebral infarction, atrial fibrillation, seizures, and infections.Conclusions Findings from this meta-analysis suggest that intrapericardial use of TXA in patients undergoing cardiac surgery can decrease postoperative bleeding without increasing the risk of postoperative seizures. Future large randomized, double-blind, controlled clinical trials are needed to confirm these promising findings.
Keywords: surgery; complications; coronary artery bypass grafting; valve surgery